Comparative analysis for penetration of distributed generation in power systems - Singh D.; Singh D.; Verma K.S. (My University, 2025)
This paper addresses comparative analysis for penetration of distributed generation (DG) from the perspective of a distribution company (disco). Penetration of distributed generator (Size and location) is obtained through different approaches: Cost minimization and System Energy loss minimization. The methodology adopted permits the planner to decide optimal location and size of DG with compromise between System cost and System energy loss. GA based approaches for penetration of DG in power systems in different loading conditions with time varying loads is explained. Minimization of the functions is performed under voltage and line loading constraints. Proposed strategy is applied to power distribution systems and its effectiveness is verified through simulation results on 16-bus and 37-bus systems with typical load. ©2008 IEEE.